Pelatihan Rancangan Kegiatan Pembelajaran Menggunakan Model Pembelajaran Inovatif Pada Guru-Guru SD Yapis 2 Merauke - Salman Alparis Sormin; Yonarlianto Tembang; Dharma Gyta Sari Harahap (Jurnal Transformasi Pendidikan Indonesia, 2023)
This training activity aims to increase the knowledge and skills of teachers at SD Yapis 2 Merauke in preparing learning activity plans using innovative learning models. This activity started with the teachers of SD Yapis 2 Merauke regarding the complex models of innovative learning development. The training method is carried out using discussion techniques, question and answer, assignments and presentations. Training activities begin with a pretest to map the initial abilities of the training participants, and at the end of the activity a posttest is carried out to measure the success of the training activities carried out. An indicator of the success of this training is if participants obtain an average score of at least 75% in the good category. Based on the results of data processing from training activities, initial test information was obtained before training for 3 people or 20% with scores still in the poor category. including 7 teachers or 46.7% in the sufficient category and 5 teachers or 33.3% in the good category and 3 teachers or 20% in the poor category. After carrying out the training, final test data information was obtained for 1 person in the fair category or 7%, and 6 teachers in the good category or 40% and 8 teachers in the very good category or 53%. Based on the data, the final test results of the activity show that it has exceeded the specified success indicators. This means that the training carried out at SD Yapis 2 Merauke was declared successful and was able to improve teacher skills.